Eclectic approach: a search for more effective assessment ways to meet EFL assessment principles - Thamrin, Nur Sehang; Madya, Suwarsih; Putro, Nur Hidayanto Pancoro Setyo; Mustakim, Siti Salina; Hassan, Aminuddin; Retnawati, Heri (Syiah Kuala University, 2023)
The current EFL curriculum for high schools in Indonesia demands integrating cognitive, affective, and psychomotor domains in assessment. Therefore, teachers must consider these domains in designing assessment instruments and use them, including in a full-online class. In this type of class, they must choose effective methods with principled eclecticism that meet the assessment principles. This study examines the teachers assessment process, from constructing the assessment devices to implementing the test in virtual classrooms. The qualitative research approach was used to explore the online-based assessments involving 16 English teachers recruited through convenience sampling techniques. Accordingly, the data were collected using virtual semi-structured interviews through a WhatsApp call. The data were analysed descriptively through a thematic analysis integrated with an interactive technique to locate and identify common patterns of meaning in a data set. The findings show that teachers used several methods to design their tests in the planning stage, considering several aspects based on the eclectic approach principles for effective assessment practices. However, teachers need more assessment literacy regarding their knowledge of test quality. This research employed qualitative data from a small number of teachers, so future studies that include more teachers from different locations and consider different viewpoints, including those of students, families, and policymakers, on how to evaluate student achievement virtually are recommended.